Association of Endocan, Ischemia-Modified Albumin, and hsCRP Levels With Endothelial Dysfunction in Type 2 Diabetes Mellitus. (August 2018) - Balamir, Ilhan; Ates, Ihsan; Topcuoglu, Canan; Turhan, Turan
We investigated the relationship of ischemia-modified albumin (IMA) and high-sensitivity C-reactive protein (hsCRP) levels with direct (endocan) and indirect (carotid intima–media thickness [cIMT] and 24 hours urine protein excretion) endothelial dysfunction indicators in type 2 diabetes mellitus (T2DM). Patients with T2DM (n = 88) and 88 healthy individuals were included in the study. The median endocan (475.15 vs 216.37 pg/mL; P < .001, respectively) and hsCRP (10.74 vs 3.11 mg/L; P < .001, respectively) and the mean IMA (0.64 ± 0.12 vs 0.51 ± 0.12 absorbance units; P < .001, respectively) levels were higher in participants with endothelial dysfunction compared to those without endothelial dysfunction in T2DM. The 24-hour urine protein excretion and cIMT levels had a positive correlation with hsCRP ( r = .357; P = .001 and r = .592; P < .001, respectively), IMA ( r = .519; P < .001 and r = .495; P < .001, respectively) and endocan ( r = .347; P = .001 and r = .583; P < .001, respectively) levels in the T2DM group. Stepwise multivariable logistic regression analysis, which included laboratory findings found to be associated with endothelial dysfunction, showed that endocan (odds ratio [OR] = 1.456; P = .004), hsCRP (OR = 1.298; P = .008), and IMA (OR = 2.270, P = .003) were independent risk factors. It was found that none of these markers were superior in terms of diagnostic discrimination for endothelial dysfunction. Endocan, IMA, and hsCRP levels were found to be associated with endothelial dysfunction in patients with T2DM.